Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1515/comm.2010.010
|View full text |Cite
|
Sign up to set email alerts
|

The digital divide among young people in Brussels: Social and cultural influences on ownership and use of digital technologies

Abstract: This article reports on a survey of youth in Brussels (N ϭ 1,005) and their ownership and use of digital technologies, focusing specifically on the social and cultural diversity within this group. Socio-cultural diversity includes differences regarding ethnicity and gender, language and educational attainment, as well as social and economic status. The relationship of these socio-cultural differences with the digital divide in terms of ownership and use is investigated. The data show a persistent ownership di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…In many other parts of the world, including Australia, Singapore, Canada, China, Belgium and OECD countries, research has similarly identified an unevenness of access and use of the Internet within their societies, based upon a range of factors not limited to age or generational factors (CDF, 2010;Cheong, 2008;Goode, 2010;Guo, Dobson, & Petrina, 2008;Kennedy et al, 2010;Li & Ranieri, 2010;Mertens & d'Haenens, 2010;OECD, 2010;PISA, 2005;Sztendur & Milne, 2009). …”
Section: The Digital Dividementioning
confidence: 99%
See 2 more Smart Citations
“…In many other parts of the world, including Australia, Singapore, Canada, China, Belgium and OECD countries, research has similarly identified an unevenness of access and use of the Internet within their societies, based upon a range of factors not limited to age or generational factors (CDF, 2010;Cheong, 2008;Goode, 2010;Guo, Dobson, & Petrina, 2008;Kennedy et al, 2010;Li & Ranieri, 2010;Mertens & d'Haenens, 2010;OECD, 2010;PISA, 2005;Sztendur & Milne, 2009). …”
Section: The Digital Dividementioning
confidence: 99%
“…Many researchers have highlighted the need for consideration of variation of both access to and use made of the Internet within populations, to avoid acceptance of ambit claims made about the role of the Internet as if it was similarly used by whole generations of people (Brown & Czerniewicz, 2010;Ferro, Dwivedi, Gil-Garcia, & Williams, 2010;Fourie & Bothma, 2006;Hargittai, 2010;Hargittai & Hinnant, 2008;Helsper, 2008;Helsper & Eynon, 2010;Kennedy et al, 2010;Mertens & d'Haenens, 2010;Rideout et al, 2010;Selwyn, 2008b;Thinyane, 2010;Underwood, 2007;Vaidhyanathan, 2008;Warschauer & Matuchniak, 2010).…”
Section: The Digital Dividementioning
confidence: 99%
See 1 more Smart Citation
“…It is also related to other social issues, such as territorial exclusion of the community or the low educational levels of its users. Often than not, the problem of social integration, migration and language directly affect this phenomenon, as was the case of some European countries, where a high percentage of young migrants or children of migrants have low education levels and a deficient use of the official language (Mertens & D'Haenens, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Typically, digital divide studies have documented the level of internet connectivity or lack of connectivity (Davison & Cotten, 2010;Goswami, 2008;Jackson, Fitzgerald, Eye, Zhao, & Witt, 2010;Strover, 2001;Dijk, 2006;Warf, 2010;Warschauer, 2004;Weinstein & Clower, 1994;Wirth, 2006) and access to a computer on a particular population or city (Dijk, 2005;DiMaggio, Hargittai, Coral, & Shafer, 2004;Hacker & Steiner, 2002;La Pastina & Quick, 2004;Malecki, 2003;Mertens & D'Haenens, 2010;Pedrozo, 2013). However, this research analyzes the digital divide question from a different perspective: the social and cultural approach of different generations within the same family focusing on how they interact with technology.…”
Section: Introductionmentioning
confidence: 99%